1998
DOI: 10.1002/(sici)1098-1004(1998)11:6<456::aid-humu6>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of pyrin gene mutations in Turks with familial Mediterranean fever (FMF)

Abstract: Familial Mediterranean fever (FMF) is an autosomal recessive disease clinically characterized by recurrent short self‐limited attacks of fever accompanied by peritonitis, pleurisy, and arthritis and can lead to amyloidosis and renal failure in the longer term. It is prevalent mainly in non‐Ashkenazi Jews, Armenians, Turks, and Arabs. Due to the lack of an accurate diagnostic test, patients often experience years of attacks and invasive diagnostic procedures before the correct diagnosis is made and adequate tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
1
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 19 publications
3
7
1
3
Order By: Relevance
“…Of the known hereditary periodic fevers, FMF is the most prevalent and best characterized. It is an autosomal recessive disorder, which predominantly affects people living in or originating from areas around the Mediterranean basin, mainly Jews, Armenians, Turks and Arabs (Chen et al, 1998;Touitou et al, 1998). Mediterranean fever (MEFV) gene has already been identified as being responsible for FMF (The International FMF Consortium, 1997).…”
Section: Introductionsupporting
confidence: 52%
“…Of the known hereditary periodic fevers, FMF is the most prevalent and best characterized. It is an autosomal recessive disorder, which predominantly affects people living in or originating from areas around the Mediterranean basin, mainly Jews, Armenians, Turks and Arabs (Chen et al, 1998;Touitou et al, 1998). Mediterranean fever (MEFV) gene has already been identified as being responsible for FMF (The International FMF Consortium, 1997).…”
Section: Introductionsupporting
confidence: 52%
“…Misdiagnosis is unlikely in these children because all had a typical history of FMF attacks and one had a strong family history. Our results probably reflect mutation spectrum of Turkish people with FMF and are consistent with those of a previous study (22).…”
Section: Discussionsupporting
confidence: 93%
“…found in 85% of the carrier chromosomes that were mainly obtained from Jewish FMF patients (10,11). Similarly, three mutations (M680I, M694V and V726A) were found in 85% of Turkish FMF patients in a recent study (22). Our unpublished data, which included 238 Turkish FMF patients, showed a similar frequency.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Since the first two main publications by the two consortia, various other studies confirmed the preponderance of the M694V mutation in north African Jews, Oriental Jews, Armenians, and Turks (Dewalle et al, 1998;Eisenberg et al, 1998;Chen et al, 1998;Shohat et al, 1999;Aksentijevich et al, 1999;Cazeneuve et al, 1999;Dodé et al, 2000). One of the other main FMF mutations, V726A (The French FMF Consortium, 1997; The International FMF Consortium, 1997), occurs relatively frequently in non-Ashkenazi Jews, Iraqi Jews, Armenians, and Turks (Chen et al, 1998;Eisenberg et al, 1998;Aksentijevich et al, 1999).…”
Section: Resultsmentioning
confidence: 99%